NDT80 transcription factor as a negative regulator for Candida parapsilosis adhesion and biofilm formation - Gomes, Nuno Miguel Araújo da Cunha (2015)
C. parapsilosis infections incidence has been increasing for the past 20 years. Its caracteristics of adhering and forming biofilms are a critical factor for infection caused by this organism, affecting from immunocompromised or transplanted patients to low-birth-weight neonates. The health-care workers are a major transmission vehicle of this fungus. The azoles class of antifungal drugs are the first and most common line of defense to treat infections by this type of yeast species. Its mode of action on the yeast cell works by inhibiting the lanoststerol 14α-demethylase, an enzyme belonging to the ergosterol biosyntethic pathway.. On a recent study it has become clear that C. parapsilosis antifungal azole resistance may display similar resistance mechanisms that the ones described for C. albicans. A resistant strain obtained after exposure to posaconazole has shown an upregulation of two transcriptional factors, Upc2 and Ndt80. The aim of this work was to assess the role of these two transcriptional factors on C. parapsilosis azole resistance. For that, it was intended to knockout both genes using the SAT1-flipper cassette. The strain obtained after disruption of one copy of NDT80 gene displayed an unexpected phenotype, concerning adhesion and biofilm formation, comparatively to the wild-type BC014 strain. It were also made susceptibility tests although with no evident changes. These results demonstrate that NDT80 gene may be a negative regulator of C. parapsilosis adherence to abiotic and biotic substrates, impairing also biofilm formation.